2004
DOI: 10.1128/mcb.24.12.5290-5303.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in a Partitioning Protein and Altered Chromatin Structure at the Partitioning Locus Prevent Cohesin Recruitment by the Saccharomyces cerevisiae Plasmid and Cause Plasmid Missegregation

Abstract: The 2m circle is a highly persistent "selfish" DNA element resident in the Saccharomyces cerevisiae nucleus whose stability approaches that of the chromosomes. The plasmid partitioning system, consisting of two plasmid-encoded proteins, Rep1p and Rep2p, and a cis-acting locus, STB, apparently feeds into the chromosome segregation pathway. The Rep proteins assist the recruitment of the yeast cohesin complex to STB during the S phase, presumably to apportion the replicated plasmid molecules equally to daughter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
84
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(91 citation statements)
references
References 34 publications
7
84
0
Order By: Relevance
“…These strains contained only the tagged version of 2m, with none of the original native plasmid (see Materials and Methods). While the plasmids expressing tagged Rep1 and Rep2 were not maintained as well as the Flp1-and Raf1-expressing plasmids (ϳ1% loss per generation for tagged Rep1 and Rep2 versus 0.3% for Flp1 and 0.08% for Raf1) (see Materials and Methods), these loss rates are an order of magnitude lower than those seen when the plasmid segregation system is inactive (34,42,44). This suggested that tagged Rep1 and Rep2 were at least partially active.…”
Section: Siz1⌬ Siz2⌬ Mutants Exist In Different Heritable Statesmentioning
confidence: 75%
See 2 more Smart Citations
“…These strains contained only the tagged version of 2m, with none of the original native plasmid (see Materials and Methods). While the plasmids expressing tagged Rep1 and Rep2 were not maintained as well as the Flp1-and Raf1-expressing plasmids (ϳ1% loss per generation for tagged Rep1 and Rep2 versus 0.3% for Flp1 and 0.08% for Raf1) (see Materials and Methods), these loss rates are an order of magnitude lower than those seen when the plasmid segregation system is inactive (34,42,44). This suggested that tagged Rep1 and Rep2 were at least partially active.…”
Section: Siz1⌬ Siz2⌬ Mutants Exist In Different Heritable Statesmentioning
confidence: 75%
“…Sumoylation of the other sites in Flp1 was Siz dependent. Several yeast proteins involved in 2m partitioning have recently been shown to be sumoylated, including the chromatin remodeling complex subunit Rsc2 and the cohesin subunits Smc1 and Scc1/Mcd1 (27,41,42,44). It is not known to what extent sumoylation of these proteins is controlled by Siz1 and Siz2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STB function depends on its association with Cse4, presumably as a nucleosome component, in a Rep1-Rep2-assisted manner (12,24, and present study). Furthermore, G1 arrest and spindle disassembly, conditions that do not foster Cse4-STB association (12) but sustain Rep-STB association (3,9,14,16), decrease Lk by the anticipated amount ( Fig. 3 A and B).…”
Section: Discussionmentioning
confidence: 99%
“…These factors include the mitotic spindle, the spindleassociated motor Kip1, the RSC2 chromatin-remodeling complex, the centromere-specific histone H3-variant Cse4 (CenH3), and the yeast cohesin complex (9)(10)(11)(12)(13)(14)(15). The de novo assembly of the plasmid-partitioning complex at STB during the G1-S window of each cell cycle (9,12,14,16) is reminiscent of the assembly of the kinetochore complex at centromeres. However, kinetochore components have not been detected at STB by ChIP (13).…”
mentioning
confidence: 99%